ADAPTABILITY OF Rhizoctonia solani AG-1 IA FOR MANCOZEB SENSITIVITY UNDER TEMPERATURE STRESS - de Oliveira, Samanta Cristiene [UNESP]; Silva, Tatiane Carla [UNESP]; Campos V., Samara Nunes [UNESP]; Ferraudo, Guilherme Moraes; Moreira, Silvino Intra [UNESP]; Ríos, Katherin Castro; Ceresini, Paulo Cezar [UNESP] (Universidad Centroccidental Lisandro Alvarado, 2022)
The genetic architecture of quantitative characters in plants can be influenced by stress due to environmental changes, in combination with the decrease in the organism’s average performance, resulting in genetic and environmental variances. The main objective of this study was to determine how the high-temperature stress affects the sensitivity of three populations of the soybean foliar blight pathogen Rhizoctonia solani AG-1 IA from Mato Grosso, Maranhão, and Tocantins to a broad-spectrum fungicide. The specific objective was to determine the effect of environmental stress on evolvability components (i.e., the selection response measures such as genotypic, environmental, and phenotypic variances) associated with sensitivity to the broad spectrum dithiocarbamate fungicide mancozeb. The fungal isolates from the three pathogen populations were grown under two temperatures (25 °C and 33.5 ºC, optimum and stress, respectively) and three fungicide concentrations (0.0, 0.32, and 0.64 g·L-1 of active ingredient). The mycelial growth was measured, and evolvability components, such as the genotypic variance coefficient (IG), the environmental variance (IE), and the broad-sense heritability (h2), were determined. The results showed that high-temperature stress decreased (≈ 0.1 units, in a scale from 0 to 1.0) the genotypic variance and the heritability for mancozeb sensitivity in three populations of the soybean foliar blight pathogen R. solani AG-1 IA.
Adaptabilidad de Rhizoctonia solani AG-1 IA a la sensitividad al mancozeb bajo estrés de temperatura tectura genética de los caracteres cuantitativos en las plantas puede verse influenciada por el estrés debido a ca
Keywords: Additional Evolvability; genetic and environmental variation; heritability; soybean foliar blight; thermal adaptability